Gestión y administración en el Hotel Capitol#2 de la ciudad de Babahoyo - Rodriguez Ortega, Francisco Yamil (2021)
Nowadays, the administrative management is responsible for the coordinated and efficient use of resources. For this reason, all the functions are organized in such a way that the most appropriate handling of these can be directed and controlled. These functions are planning, organization, direction, coordination and control. In addition, administrative management allows, through the rational management of tasks, efforts and resources, to prevent future problems and above all to achieve favorable results for the company. The investigation called “Management and Administration in the Hotel Capitol L # 2 of the City of Babahoyo, had as objective to analyze the factors that cause an inadequate Administrative Management, and how it affects the inadequate attention to which a descriptive investigation was applied. The existing problems in the Hotel Capitol were addressed based on the quality Administrative management of the same, all these problems appear in the development. The methodology used in this study was qualitative and quantitative, the techniques and instruments that were used to collect more information were: an interview with the owner of the Hotel and a survey prepared for the people who stay in the Capitol, obtaining results that allowed reach a general conclusion of the present case study, which was supported with bibliographic references, these helped to understand in a scientific way the depth of this research.